Academic Administration Information System for Junior High School (SMP) PGRI Bengkulu City - Andri Maryensyah; Indra Kanedi; Ricky Zulfiandry (Jurnal Komputer, Informasi dan Teknologi, 2021)
SMP PGRI Bengkulu City is one of the schools in Bengkulu Province. In the process of managing academic data, most of them are still done manually and have also used office application packages in managing data, namely Microsoft Excel. The problem that often occurs is the absence of an integrated system that is able to manage academic data as a whole, so that data management takes a long time. The Academic Administration Information System for Junior High School (SMP) PGRI Bengkulu City was created using the PHP programming language and MySQL database. The features contained in the Academic Information System are operator data processing, student data, teacher data, class data, subject data, student grade data, teacher data recap, student data recap, subject data recap per class, grade recap per subject. In this academic information system, there are 3 access rights, namely Operator, Teacher, and Student, each of which has different features. Based on the results of the tests that have been carried out, the Academic Information System at the PGRI Bengkulu City Junior High School (SMP) has been running as it should.